2014
DOI: 10.3390/ijms15045623
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Receptor rs7529229 T/C Polymorphism Is Associated with Left Main Coronary Artery Disease Phenotype in a Chinese Population

Abstract: Left main coronary artery disease (LMCAD) is a particular severe phenotype of coronary artery disease (CAD) and heritability. Interleukin (IL) may play important roles in the pathogenesis of CAD. Although several single nucleotide polymorphisms (SNPs) identified in IL related genes have been evaluated for their roles in inflammatory diseases and CAD predisposition, the investigations between genetic variants and CAD phenotype are limited. We hypothesized that some of these gene SNPs may contribute to LMCAD phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
(34 reference statements)
1
17
0
1
Order By: Relevance
“…Yu et al (2012) conducted a study in a Korean population, and reported that the IL-10 -592C/A and -819C/T gene polymorphisms might be associated with ischemic heart disease. However, in one study in a Chinese population, it was reported that IL-10 gene polymorphism was not correlated with the risk of CAD (He et al, 2014). In contrast, in a recent meta-analysis of 14 case-control studies with a total of 5006 patients and 3968 controls, it was reported that the IL-10 -1082 gene polymorphism might be associated with an increased overall risk of CAD, especially in Caucasians (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Yu et al (2012) conducted a study in a Korean population, and reported that the IL-10 -592C/A and -819C/T gene polymorphisms might be associated with ischemic heart disease. However, in one study in a Chinese population, it was reported that IL-10 gene polymorphism was not correlated with the risk of CAD (He et al, 2014). In contrast, in a recent meta-analysis of 14 case-control studies with a total of 5006 patients and 3968 controls, it was reported that the IL-10 -1082 gene polymorphism might be associated with an increased overall risk of CAD, especially in Caucasians (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Several previous studies have reported the association between IL-10 gene polymorphisms and CAD risk, but these results have also been controversial Jin et al, 2013;Elsaid et al, 2014;He et al, 2014). Elsaid et al (2014) conducted a case-control study in an Indian population, and reported that the C allele of IL-6 -174G/C (rs1800795) and the G allele of IL-10 -1082A/G (rs1800896) were associated with an increased risk of CAD.…”
Section: Discussionmentioning
confidence: 98%
“…One animal experimental study has shown that several cytokines play a key role in the development of CAD (Kleemann et al, 2008). Several previous epidemiology studies have shown that polymorphisms in several cytokines, including interleukin-6 (IL-6), , are involved in the pathogenesis of CAD (Zhang et al, 2011;Huang et al, 2013;Opstad et al, 2011Opstad et al, , 2013Galimudi et al, 2014;He et al, 2014;Zhang et al, 2014). However, the results of these studies are inconsistent.…”
Section: Introductionmentioning
confidence: 39%
“…Many epidemiologic studies have observed that polymorphisms in the genes encoding interleukin-1 receptor antagonist, such as , are associated with the development of CAD (Zhang et al, 2011;Huang et al, 2013;Opstad et al, 2011Opstad et al, , 2013Galimudi et al, 2014;He et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that sequence variations in this gene are associated with CAD, but their results have been inconsistent (Vogiatzi et al, 2008;He et al, 2014;Ren and She, 2015;Yang et al, 2015). Vogiatzi et al (2008) conducted an investigation into the influence of common IL-8 polymorphisms on CAD risk, showing a combination of the -251A/ T and -781C/T variants to be associated with susceptibility to this disease.…”
Section: Discussionmentioning
confidence: 99%